The impact of a 14-day altitude training camp on olympic-level open-water swimmers' sleep - Vitale, J. A.; Ieno, C.; Baldassarre, R.; Bonifazi, M.; Vitali, F.; La Torre, A.; Piacentini, M. F. (International Journal of Environmental Research and Public Health, 2022)
Despite the common belief that sleep quality at altitude is poor, the scientific evidence to support this notion is still modest. Therefore, the purpose of the present study was to evaluate possible changes of actigraphy-based and subjective sleep parameters in a group of elite open-water swimmers during a 14-day altitude training camp (ATC) at 1500 m. The study subjects were five Olympic-level open-water swimmers (mean age: 25.0 ± 3.2 years; 3 females and 2 males). All subjects wore a wrist activity monitor and filled a sleep diary for 18 consecutive nights, 4 nights before and 14 nights during ATC. The data were then analyzed at four different time points: before ATC (PRE), the first two days of ATC (T1), and after one (T2) and two weeks of ATC (T3). Training load, assessed as the covered distance (km), session rating of perceived exertion (sRPE), and heart rate (HR), was monitored during the week before and the first and second week of ATC. No significant differences in objective and subjective scores of sleep quality were detected, whereas the sleep onset time (p = 0.018; Eta2p = 0.83, large) and sleep offset time (p < 0.001; Eta2p = 0.95, large) significantly differed among PRE, T1, T2, and T3: elite athletes started to sleep and woke up ~ 1 h earlier the first two days of ATC compared to PRE (sleep onset time: p = 0.049; sleep offset time: p = 0.016). Further, an increase in the training volume during the two weeks of the ATC was observed, with the most time spent in a low-intensity regime and an increase in time spent in a high-intensity regime compared to PRE. Sleep quality was not negatively influenced by a 14-day altitude training camp at 1500 m in a group of Olympic-level elite swimmers despite an increase in perceived exertion during training sessions. Nonetheless, early sleep onset and sleep offset times were observed for the first two nights of ATC: elite athletes started to sleep and woke up ~ 1 h earlier compared to the baseline nights.